Vocational Education and Training in the Baltic Sea Region as Impact for Entrepreneurship and Regional Development : Analytical Highlights of Trends, Innovations and Projects - French, Martin [Verfasser]; Diettrich, Andreas [Verfasser]; Rose, Philipp [Verfasser]; Eichenmüller, Luise [Verfasser] (My University, 2016)
"This publication gives on the one hand a highlighted overview of current trends, innovations and potentials of VET systems in the BSR countries Estonia, Latvia, Lithuania, Poland, Germany, Denmark, Sweden and Finland. These analytical highlights are therefore focussing the different national "States of Play" in the BSR regions regarding their VET systems, but also give some impressions concerning systemic internationalisation of VET or possibilities of interregional VET collaboration. These contributions are presenting a more top-down view of VET, also taking into account the national strategies of implementing European education policy and the EUSBSR. On the other hand the publication shows the immense "development power" that funded VET projects in the BSR can have on "(Inter)Regional VET Innovation Systems". For this the publication will describe the "VET reality" regarding international/interregional VET cooperation and projects in the BSR in the last years while presenting a selection of relevant funded BSR projects with a project focus or aspects regarding VET (including important thematically related projects with focus i.e. human capacity building, labour market policy, school to work transition, entrepreneurship/intrapreneurship education, SME internationalisation etc.). So this could be seen as a shortened compendium of relevant projects dealing with VET issues in the BSR. All these contributions lead to the fact, that if the BSR would like to be a model region of sustainable interregional VET cooperation, potentials and innovations should be discussed mutually and transparently between VET stakeholders/decision-makers in the BSR. Furthermore projects, funded by the various funding programmes with regional scope on the BSR and as "bottom-up VET development tools", should be strengthened for international/interregional VET collaboration "at the base"." (Editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 1 Internationale Berufsbildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildung; Internationale Zusammenarbeit; Baltikum; Estland; Lettland; Litauen; Polen; Dänemark; Schweden; Finnland; Bundesrepublik Deutschland